Solving fractional nonlinear partial differential equations by the modified Kudryashov method. (August 2019) - Hao, Menghan; Zhang, Yanni; Pang, Jing
Abstract: There are more and more methods for transforming nonlinear partial differential equations into ordinary differential equations by using the traveling wave transform. In this paper, the modified Kudryashov method is used to use the new traveling wave transform, and the exact solution of the space-time fractional equal-width equation is obtained by means of symbolic computation. Search for solution of the equal-width equation becomes more direct and simple. It is also suitable for solving a large number of similar fractional-order nonlinear partial differential equations, the method provides a new idea for solving fractional-order nonlinear partial differential equations.